There is no convincing evidence that working memory training is effective: A reply to Au et al. (2014) and Karbach and Verhaeghen (2014) - Melby-Lervåg, Monica; Hulme, Charles (Psychonomic bulletin & review, 2016)
The possible cognitive benefits of working memory training programs have been the subject of intense interest and controversy. Recently two meta-analyses have claimed that working memory training can be effective in enhancing cognitive skills in adulthood (Au et al. Behavioural Brain Research 228:(1) 107-115, 2014) and stemming cognitive decline in old age (Karbach & Verhaeghen Psychological Science 25:2027–2037, 2014). The current article critically evaluates these claims. We argue that these meta-analyses produce misleading results because of (1) biases in the studies included, (2) a failure to take account of baseline differences when calculating effect sizes, and (3) a failure to emphasize the difference between studies with treated versus untreated control groups. We present new meta-analyses and conclude that there is no convincing evidence that working memory training produces general cognitive benefits.